Safe right bundle branch block pattern during permanent right ventricular pacing: a case report - Abdelkarim Errahmouni; Jean Christophe Charniot; Jean Yves Artigou (KARE Publishing, 2013)
We present the case of a 72-year-old male who underwent a permanent transvenous DDD pacemaker implantation for symptomatic complete heart block. The postoperative surface electrocardiogram (ECG) revealed a right bundle branch block (RBBB) pacing pattern with transition in lead V3 and left bundle branch block (LBBB) in D1, suggesting a malpositioned ventricular lead in the left heart. Malposition of a lead was ruled out by chest X-ray and echocardiogram confirming apical right ventricular pacing. After a literature review, a surface ECG maneuver, by placing leads V1 and V2 one intercostal space lower, restored the usual patterns of paced LBBB pattern. We discuss the literature concerning safe-paced RBBB.